Three Levels of Geomembrane Puncture Protection. Issue 4 (1995) - Narejo, D.B.
Abstract : Depending on the application in which geomembranes are used, they may require different levels of protection from puncture. The required thickness and mass per unit area of a protection material for any application depends on the consequences of leakage through the geomembrane. This technical note proposes three levels of protection for high density polyethylene geomembranes, depending on the expected damage to the environment. Level I protection is suggested for hazardous waste systems, Level II for nonhazardous waste systems, and Level III for temporary or other noncritical applications. Examples of the each protection level are provided.